"Notas sobre el Eufemismo en Tucidides" - Benavente, Mariano (Florentia Iliberritana, 2016)
The greek word εuιφημισμóς is relatively tardy (Cf. Eust - 1938-52; Demetr. Eloe. 281; Com. ND 21; Hermog - Prog - 7; etc.). Howsoever, the notion and use of euphemism occurs in authors as Thucydidis and Plato. The euphemism comprises diverse lexical ambits (taboo of the dread, pudicity's taboo, delicacy's taboo, etc.). In the work of Thucydidis the euphemism appears well in all these ambits; the following texts: 11 50-2 and VI 57-4 (delicacy's taboo); I 48-4, III 107-4 and VI 67-1 (taboo of the dread); II 3-2 and II 49-8 (pudicity's taboo). the texts are only examples. The totality of the euphemism in this author requires a more broad study than the present trial.